2021
DOI: 10.1111/cas.14794
|View full text |Cite
|
Sign up to set email alerts
|

Expression of asporin reprograms cancer cells to acquire resistance to oxidative stress

Abstract: Asporin (ASPN), a small leucine‐rich proteoglycan expressed predominantly by cancer associated fibroblasts (CAFs), plays a pivotal role in tumor progression. ASPN is also expressed by some cancer cells, but its biological significance is unclear. Here, we investigated the effects of ASPN expression in gastric cancer cells. Overexpression of ASPN in 2 gastric cancer cell lines, HSC‐43 and 44As3, led to increased migration and invasion capacity, accompanied by induction of CD44 expression and activation of Rac1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Taken together, these data suggest that the features of CEFs evaluated in this study were unlikely to have been induced by TGF- CEFs induced cancer cell spreading via IL-1 secretion, which activates Rac1 in cancer cells. Moreover, ASPN upregulates CD44 expression and activates Rac1 via interaction with CD44 on the cell membrane [16,33], which also increases cancer cell spreading (Fig. 7A).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Taken together, these data suggest that the features of CEFs evaluated in this study were unlikely to have been induced by TGF- CEFs induced cancer cell spreading via IL-1 secretion, which activates Rac1 in cancer cells. Moreover, ASPN upregulates CD44 expression and activates Rac1 via interaction with CD44 on the cell membrane [16,33], which also increases cancer cell spreading (Fig. 7A).…”
Section: Discussionmentioning
confidence: 98%
“…As a downstream target of NF-B signaling, ASPN is upregulated because its promoter contains a binding site for NF-B p65 [41]. In turn, ASPN further increases NF-B and HIF-1 expression [33] (Fig 7A). Therefore, ROS production is a major trigger of the inflammatory response in CEFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier study found that Asporin played an important role in osteoarthritis, rheumatoid arthritis and lumbar disc degeneration and other bone and joint diseases by affecting the formation and differentiation of bone and cartilage [17][18]. Recently, some studies have con rmed that Asporin is secreted by CAFs and can promote the invasion of tumor cells by binding with CD44 receptor in a variety of human cancers [13,[19][20]. Those studies suggest that Asporin could be a new potential target for human cancer treatment targeting the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Whether SFN diminishes CD44s in parallel and whether SFN action on CD44 correlates with oxidative stress requires further investigation. Sasaki’s work has indicated a close interaction between CD44s and HIF1α-mediated resistance to oxidative stress [ 153 ], and Xu et al have shown that reduced CD44s expression correlates with induced intracellular levels of ROS in bladder cancer cells [ 154 ]. It seems likely, therefore, that SFN’s action on CD44 expression is linked to ROS and ROS-related pathways.…”
Section: Sfn In Bladder Cancermentioning
confidence: 99%